Utilisation of second-trimester spontaneous and induced abortion services in public hospitals in Mexico, 2007–2015. Issue 4 (14th August 2019) - Alexander, Lily T; Fuentes-Rivera, Evelyn; Saavedra-Avendaño, Biani; Schiavon, Raffaela; Maldonado Rueda, Noe; Hernández, Bernardo; Drake, Alison L; Darney, Blair G
Abstract : Background: Data on utilisation of in-facility second-trimester abortion services are sparse. We describe temporal and geographical trends in utilisation of in-facility second-trimester abortion services across Mexico. Methods: We used 2007–2015 data from Mexico's Automated Hospital Discharge System (SAEH) to identify second-trimester abortive events (ICD O02-O08) in public hospitals across Mexico's 32 states. We described utilisation, calculated rates using population data, and used logistic regression to identify woman- and state-level factors (municipality-level marginalisation, state-level abortion law) associated with utilisation of second-trimester versus first-trimester services. Results: We identified 145 956 second-trimester abortions, or 13.4% of total documented hospitalizations for abortion between 2007 to 2015. The annual utilisation rate of second-trimester abortion remained constant, between 0.5 to 0.6 per 1000 women aged 15–44 years. Women living in highly marginalised municipalities had 1.43 higher odds of utilising abortions services in their second versus their first trimester, when compared with women in municipalities with low marginalisation (95% CI 1.18 to 1.73). Living in a state with a health or fetal anomaly exception to abortion restrictions was not associated with higher utilisation of second-trimester abortion services. Conclusions: Our results suggest there is a need for all types of second-trimester abortion services in Mexico. To improve health outcomes for Mexican women, especially the most vulnerable, access to safe second-trimester abortion services must be ensured through the implementation of current legal exceptions and renewed attention to the training of healthcare providers.